A collection of Rudyard Kipling's Just so stories - Kipling, Rudyard 1865-1936 (Candlewick Press, 2004)
A collection of stories originally told by Rudyard Kipling to his daughter, that deal with such issues as How did the Rhinoceros get his wrinkly skin? and Why won't cats come when they're called
Keywords: Children's stories, English; Animals / Fiction; Short stories; Children's stories; Juvenile works; Fiction; Juvenile literature; Kinderbuch; Anthologie